Perfil imunomodulador DO ? -benzilideno digoxina 8 (BD-8) em macrófagos peritoneais murinos - Ferreira, Davi Azevedo (2024)
Cardiotonic Steroids (CTS) are natural compounds with various biological activities that can interact with and inhibit Na+/K+-ATPase. The secretion of some of these steroids (marinobufagin and ouabain) is stimulated by increased plasma sodium concentration, angiotensin II, and adrenocorticotropic hormone (ACTH). CTSs can modulate the immune system's activity, acting in the inflammatory process by regulating molecules such as Mitogen-Activated Protein Kinases (MAPK) p38, CD18, and Nuclear Factor kappa-B (NF-κB). The new semi-synthetic CTS, BD-8, is derived from digoxin. However, the biological effect of this new compound is unknown. Therefore, the present study aimed to investigate the immunomodulatory activity of BD-8 in vitro and uncover the possible mechanisms involved in this activity. For this purpose, female Swiss mice were pre-stimulated with an intraperitoneal (i.p.) injection of thioglycolate to harvest peritoneal macrophages for culture. The cells were stimulated with zymosan (ZYM) (0.2 mg/mL) and/or treated with different concentrations of BD-8 (1nM, 10nM, 100nM, 1μM, 10μM, 100μM). The cells were subjected to an MTT assay (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) to determine cytotoxicity and an assay for nitric oxide (NO) measurement using the Griess solution. Cytokine levels (IL-1β, IL-6, TNF-α, and IL-10) were measured using a sandwich-type enzyme-linked immunosorbent assay (ELISA). Phagocytic capacity was assessed by two assays, both in 24-well plates (5x10⁶ cells/well) by analyzing the amount of ZYM phagocytosed, considered phagocytic when more than three ZYM particles were phagocytosed, and by an assay with RedZYM fluorescent particles subsequently analyzed by flow cytometry. For cellular signaling, cells were fixed, permeabilized, and stained with antibodies against Akt, mTOR, iNOS, p-p38, p-ERK1/2, p-NF-κB, p-Src, and COX-2. Cells were adjusted to 1x10⁶ cells/tube and 10,000 events were read in a flow cytometer. Results showed that BD-8 did not exhibit cytotoxic activity at the tested concentrations of 10 and 1μM, and 100, 10, and 1nM. NO production was negatively modulated by BD-8 at concentrations of 1μM (19.40%) and 10μM (32.08%). Treatment with BD-8 at 10μM reduced IL-1β levels by 17%, while at 100nM, it increased IL-10 levels by 39%. The phagocytic capacity of ZYM in macrophages was decreased in the group treated with 10μM (13.5%), and at the same concentration, it reduced RedZYM particle phagocytic activity (36%). BD-8 negatively modulated the iNOS, Akt/mTOR, p38/ERK, NF-κB translocation, and Src pathways, but did not affect ROS and COX-2. Therefore, this study contributes to a better understanding of the biological effects of BD-8 and the immunological role of this cardiotonic steroid.